Discourse strategies in Pulaar the use of focus - Sonja Fagerberg (Studies in African Linguistics)
This paper uses the concept of discourse cohesion as a basis for looking at certain sentence emphasis patterns in Pulaar (Fula). In particular, four patterns of focus are examined, first syntactically and then pragmatically. Focus in Pulaar can be divided according to clefting and pseudo-clefting patterns for subject and non-subject focus. These four patterns are discussed in depth. Then, I suggest that the idea of discourse connectedness provides a model for explaining the choice of a focus pattern in a given environment. Examples of this are drawn from a transcription of the story of Gelaajo Ham Bod'eejo, performed by Mammadu Non Gii se, a griot from northern Senegal.